Sonic Logging Vs PIT untuk Mendeteksi Integritas Pondasi Tiang - Liong, Gouw Tjie (Bina Nusantara University, 2011)
Non destructive testing on piles can be divided into two main categories. The first category is to find out the integrity of the piles, such as pile integrity testing (PIT) and sonic logging. The second category is to find out the pile capacity, such as dynamic load testing/pile driving analysis. Since the early 1990s, the application of the tests was brought into practice and gained its popularity in Indonesia. However, the basic theory behind the testing has not been widely disseminated. This study tries to elaborate the first category of the testing, i.e. the pile integrity testing and sonic logging. The basic theory, the advantages and disadvantages, the application, the limitation and the interpretation of those techniques shall be discussed. Comparison on case studies of those testing methods also shall be given.